Dual‐Crosslinked Dynamic Hydrogel Incorporating Mo154 with pH and NIR Responsiveness for Chemo‐Photothermal Therapy. Issue 40 (11th August 2021) - Guedes, Gabriela; Wang, Shiqi; Fontana, Flavia; Figueiredo, Patrícia; Lindén, Jere; Correia, Alexandra; Pinto, Ricardo J. B.; Hietala, Sami; Sousa, Filipa L.; Santos, Hélder A.
Abstract: Polyoxometalates are an emerging class of molecular clusters, with well‐defined structures and chemical compositions that are produced through simple, low‐cost, and highly reproducible methods. In particular, the wheel‐shaped cluster Mo154 is a promising photothermal agent due to its intervalence charge transfer transitions. However, its toxicity hinders its systemic administration, being the development of a localized delivery system still incipient. Herein, an injectable and self‐healing hydrogel of easy preparation and administration is developed, incorporating both Mo154 and doxorubicin for synergistic photothermal and chemotherapy applications. The hydrogel is composed of benzylaldehyde functionalized polyethylene glycol, poly( N ‐isopropylacrylamide) functionalized chitosan and Mo154 . The gelation occurs within 60 s at room temperature, and the dual crosslinking by Schiff base and electrostatic interactions generates a dynamic network, which enables self‐healing after injection. Moreover, the hydrogel delivers chemotherapeutic drugs, with a release triggered by dual near infra‐red (NIR) radiation and pH changes. This stimuli‐responsive release system along with the photothermal conversion ability of the hydrogel allows the simultaneous combination of photothermal and chemotherapy. This synergic system efficiently ablates the cancer tumor in vivo with no systemic toxicity. Overall, this work paves the way for the development of novel Mo154 ‐based systems, incorporated in self‐healing and injectable hydrogels for dual chemo‐photothermal therapy. Abstract : A dual pH‐ and near infra‐red (NIR)‐responsive hydrogel is developed composed of benzylaldehyde functionalized poly(ethylene glycol), poly( N ‐isopropylacrylamide) functionalized chitosan, and a polyoxometalate Mo154 . Crosslinked by Schiff base and electrostatic interactions, the hydrogel has dynamic networks, injectability, and fast self‐healing properties. Combining doxorubicin and NIR laser irradiation, the hydrogel shows thermal ablation of cancer cells and simultaneous release of drugs for chemo‐photothermal therapy.